Analysis of Vendor Selection Strategies for Truck Procurement Using the AHP Method at PT Winson Logistics - Liem Bambang Sugiyanto, Sri Handoko Sakti, Muhammad Ikhsan, Junaidi Hendro, Muhammad Natser, (Pascasarjana STIE Amkop Makassar, 2024)
This study examines the truck procurement process at PT Winson Logistics, a company in the trucking industry, using the Analytic Hierarchy Process (AHP) method to select the best vendor. Given the competitive challenges and increasing demand for logistics services, choosing the right vendor is crucial for supporting operational efficiency, quality, and sustainability. AHP is chosen for its ability to break down complex problems into decision hierarchies that are easier to analyze, while allowing for both qualitative and quantitative assessments. The vendor evaluation criteria include price, product quality, delivery time, after-sales service, and vendor reputation. The analysis reveals that after-sales service and product quality play a critical role in vendor selection decisions. This study provides recommendations to the management of PT Winson Logistics in formulating procurement strategies based on structured analysis and demonstrates that AHP can enhance the accuracy and objectivity of the procurement decision-making process.. Keywords: Vendor Selection, Truck Procurement, Analytic Hierarchy Process (AHP).